2013
DOI: 10.1111/liv.12237
|View full text |Cite
|
Sign up to set email alerts
|

MMP‐2 is a disease‐modifying gene in primary sclerosing cholangitis

Abstract: Matrix metalloproteinase-2 C to T-1306 gene promoter polymorphism in PSC is an independent risk factor for disease severity as reflected by the need for OLT or disease progression leading to mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…In addition, an association of MMP-2 -1306 C/T was found with disease severity in PSC, although concomitance with IBD did not change the association strength (Korkmaz et al, 2014). The MMP-9 -1562 C/T genotype was not found to be associated with disease severity in PSC (Korkmaz et al, 2014). A highly significant association was found between overtransmission of the 5A allele in MMP-3 and CD (Pender et al, 2004).…”
Section: Mmp Genetic Association Studiesmentioning
confidence: 82%
See 1 more Smart Citation
“…In addition, an association of MMP-2 -1306 C/T was found with disease severity in PSC, although concomitance with IBD did not change the association strength (Korkmaz et al, 2014). The MMP-9 -1562 C/T genotype was not found to be associated with disease severity in PSC (Korkmaz et al, 2014). A highly significant association was found between overtransmission of the 5A allele in MMP-3 and CD (Pender et al, 2004).…”
Section: Mmp Genetic Association Studiesmentioning
confidence: 82%
“…Moreover, the MMP-3 5A allelic frequency, carriage rate and homozygosity rates were increased in PSC compared with UC, although no differences were found between UC and healthy subjects. In addition, an association of MMP-2 -1306 C/T was found with disease severity in PSC, although concomitance with IBD did not change the association strength (Korkmaz et al, 2014). The MMP-9 -1562 C/T genotype was not found to be associated with disease severity in PSC (Korkmaz et al, 2014).…”
Section: Mmp Genetic Association Studiesmentioning
confidence: 83%
“…It has been shown that activated MMP-2 is frequently observed in tumor sites, and is associated with poor prognosis of many types of cancer including melanoma, colorectal, breast, ovarian, lung and prostate cancer (37). The -1306 polymorphic site of MMP-2 is located upstream of the MMP-2 gene and may affect the protein expression by modulating its transcription, hence leading to the occurrence of human diseases, such as bladder cancer and sclerosing cholangitis (38,39); A variety of transcription factors, such as activator protein-1 (AP-1), specificity protein-1 (SP-1) and activator protein-2 (AP-2), have binding sites at the MMP-2 promoter region to regulate transcription of the MMP-2 gene (40,41). For instance, when the C nucleotide is substituted by T at MMP-2 -1306, the SP-1 binding region is inactivated, thus inhibiting the transcription and as a result the translation of MMP-2 (42).…”
Section: Discussionmentioning
confidence: 99%
“…Sample size in our present study is limited as congenital cases have low frequencies, taking into account that CI rate is proximally 4.7% [22], and the difficulties in follow-up to confirm CI; therefore it will require confirmation in larger independent cohorts. Since this is an association to several diseases [23,24]. rs243866 is another functional polymorphism in MMP2, located immediately 5' to a half-palindromic potential estrogen receptor binding site [25].…”
Section: Discussionmentioning
confidence: 99%
“…In the case of MMP9 polymorphism corresponding to the microsatellite rs2234681 ((CA) [14][15][16][17][18][19][20][21][22][23][24] repeats), capillary electrophoresis was performed after PCR, using a forward labelled and a reverse unlabeled primer sequences (Supplementary Table 1), taken from Metzger et al, 2012 [16]. Peak analysis was done applying Peak Scanner Software v1.0 (Applied Biosystems) and alleles were grouped as low (L) when the number of CA repeats was less than 21 and as high (H) when the number of CA repeats was 21 or more [17].…”
Section: Subjects and Samplesmentioning
confidence: 99%